Confrontation of tourism crime and its effects on sustainable tourism in Algeria - hadj mebtouche; ali aissa (مجلة الاجتهاد للدراسات القانونية والاقتصادية, 2019)
Security and stability can only be achieved through the middle -term and long-term planning strategy adopted by Algeria through five-year plans. In this context, social security and tourism security were an important part of the strategy adopted by the Algerian state, That national security in general cannot be achieved unless its components of economic, political and social security are realized, and tourism security as a part of economic security, it contributes significantly to the development of the tourism sector if the state works to promote the foundations on which it is based, Attached Algeria is preparing a legal system that protects the public interests of the state and the citizen from any risks that may be posed by incoming or local tourism and in the same context aimed at protecting the tourist.